2017
DOI: 10.1016/j.afos.2017.08.097
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and epidemiological profile of hip fractures in Indian population: A case-control study

Abstract: ObjectivesThis analytic retrospective case-control study was designed to analyze risk factors and the epidemiological profile of hip fractures among the Indian population with special importance to the mechanism of injuries.MethodsPatients of hip fractures (n = 41) and age- and sex-matched healthy volunteers (n = 41) were interviewed by a questionnaire regarding the occurrence of the fracture, past history of diseases and long-term medication usage, past and physical activity, supplements, smoking, and alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
0
9
0
3
Order By: Relevance
“…Ahuja et al in a retrospective study of risk factors and epidemiological profile of hip fractures in 41 patients concluded that simple measures like high friction bathroom tiles, bedside and wall side railings, trochanteric hip pads, adequate lighting play a significant role in reducing hip fractures. 19 Dhanwal et al described the first hip fracture incidence study from Rohtak district of India and found it to be same as of other Asian countries like china, Iran and South Korea. 8 Our study did not describe incidence rates as it is unlikely that all patients with hip fractures will visit our hospital for treatment.…”
Section: Resultsmentioning
confidence: 81%
“…Ahuja et al in a retrospective study of risk factors and epidemiological profile of hip fractures in 41 patients concluded that simple measures like high friction bathroom tiles, bedside and wall side railings, trochanteric hip pads, adequate lighting play a significant role in reducing hip fractures. 19 Dhanwal et al described the first hip fracture incidence study from Rohtak district of India and found it to be same as of other Asian countries like china, Iran and South Korea. 8 Our study did not describe incidence rates as it is unlikely that all patients with hip fractures will visit our hospital for treatment.…”
Section: Resultsmentioning
confidence: 81%
“…The most common mode of injury in our study was due to fall at home 19(67.85%) in females. Ahuja et al did an analytic retrospective case control study of 41 patients and 41 matched volunteers and found falls due to slipping as the major factor leading to fracture neck of femur [11] . 26(54.16%) of femora head sample showed features of degenerative changes in form of chondromalacia.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Approximately, 37 pelvic fractures per 100,000 annually have been reported in Western Europe and the United States out of which only 10% cases involve acetabulum while 17.7% cases of acetabular fractures have been reported in Indian population. 3,4 Most of the acetabular fractures occur due to high-energy trauma like road accidents (80.5%) and fall from height (10.7%). 5 Apart from this, fragility acetabular fractures are caused by low-energy fall from standing height in osteoporotic patients.…”
Section: Introductionmentioning
confidence: 99%